Athletic profile of alpine ski racers : A systematic review - Ferland, P. M.; Comtois, A. S. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to review all anthropometric and physical test results performed on alpine ski racers that were published in the scientific literature to build an athletic profile specific to the skier's sex and level. Four electronic databases were systematically searched using the following key words: alpine, skiing, and physiology. The manual search was performed through the reference list of all suitable publications, the author's personal collection, and the proceedings of the International Congresses on Science and Skiing. The search and selection strategy permitted to gather data from 28 peer-reviewed publications that were collected on a total of 1,107 skiers coming from 11 different countries. Results of this study present the athletic profile and also review the different testing protocols. Findings show that men generally present higher test results than women and that higher-level ski racers generally present higher test results than lower-level ski racers. The present review should serve as guidelines for professionals working with alpine ski racers because most of the factors presented in the athletic profile have previously been shown to be related with performance. Further research should include more details on the testing protocols used, be directed toward female athletes, and present results from groups of athletes of the same sex and clearly identified as established at a certain level. These measures could help support further theoretical investigations.